STRATEGI PENATAAN KEGIATAN PENAMBANGAN EMAS TANPA IZIN DI DESA LEBONG TAMBANG KECAMATAN LEBONG UTARA KABUPATEN LEBONG - Frandy Dwi Permana Putera; Reflis; Yurike Yurike; Urip Santoso; Enggar Aprianto (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
Illegal Gold Mining (PETI) in Lebong Tambang Village has caused various environmental, social, and economic problems. PETI activities contribute to environmental pollution due to the use of mercury, infrastructure damage, and worker safety and health risks. This study aims to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) that influence PETI management, and to formulate appropriate strategies in implementing mining regulations. This study uses a descriptive method with SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to determine the optimal strategy in PETI management. Data were collected through field observations and interviews with illegal miners and the Mining Inspector of the Ministry of Energy and Mineral Resources for the Bengkulu Province Region. The results of the analysis show that the main factors influencing PETI sustainability are limited regulation socialization, weak law enforcement, and high costs of the community mining legalization process. Recommended strategies include increasing mining regulation socialization, determining Community Mining Permits (IPR), and collaboration between local governments and mining companies in adjusting mining business permits. The implementation of this strategy is expected to create more sustainable mining, reduce environmental impacts, and improve community welfare.   Keywords : Community Mining Permit, Environment, Illegal Gold Mining, SWOT